5x-4(x+2)=-3

Simple and best practice solution for 5x-4(x+2)=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-4(x+2)=-3 equation:


Simplifying
5x + -4(x + 2) = -3

Reorder the terms:
5x + -4(2 + x) = -3
5x + (2 * -4 + x * -4) = -3
5x + (-8 + -4x) = -3

Reorder the terms:
-8 + 5x + -4x = -3

Combine like terms: 5x + -4x = 1x
-8 + 1x = -3

Solving
-8 + 1x = -3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 1x = -3 + 8

Combine like terms: -8 + 8 = 0
0 + 1x = -3 + 8
1x = -3 + 8

Combine like terms: -3 + 8 = 5
1x = 5

Divide each side by '1'.
x = 5

Simplifying
x = 5

See similar equations:

| 6(2y-3)=4y-8-2y | | 5j=6j+9 | | 25=-m-9+3m | | 5x+5=4x+17 | | (x^2+6x-7)(2x^2-5x-3)=0 | | 8-7(y+2)= | | 17-7=-2 | | 2s^2+15=-11s | | b+9b+5=-9+3b | | -2(4n-4)=3-3n | | -2=7-3(2z+3) | | 280x+135y=83300 | | b-2.8=0.86+1 | | -1+2x=6+11 | | -13=5+2a | | (3x+24)=(8x-11) | | Y+(2.8)=4.3 | | 2.50+4.25g=15.25 | | 4x+34=-7(x-8) | | x^4-6x^3+9x^2+4x-1=0 | | 5/4u=1/8 | | 13x+19y+8z=72500 | | 10x-2x=32 | | B=0.8b+4.0 | | F(X)=5x^2-14x+8 | | 2x-3=13x+30 | | -2(5x+4)+3y=-1 | | x-.85x=120 | | x-.85=120 | | 35c-4c+4c-34c=46 | | 12y=10x-14 | | 27n-22n-4n-1=42 |

Equations solver categories